The latent profile structure of negative emotion in female college students and its impact on eating behavior: the mediating role of physical exercise - Huang, Wenying; Chen, Bin; Hu, Chang (Frontiers in Public Health, 2025)
ObjectiveNegative emotions (NE) are strongly linked to disordered eating among female university students, yet the underlying mechanisms require further clarification. This study aimed to investigate the relationship between NE and eating behavior (EB) within this population, specifically examining the mediating role of physical exercise (PE) and exploring the latent profiles of NE through a person-centered approach.MethodsAn online survey was administered to 832 female university students, from which 789 valid responses were analyzed. We utilized the Depression Anxiety Stress Scale (DASS), the Sakata Eating Behavior Scale short form (EBS-SF), and a single-item PE measure. The data were analyzed using mediation analysis with bootstrapping and Latent Profile Analysis (LPA).ResultsNE was significantly and positively related to problematic EB (β = 0.414, p < 0.001) and negatively related to PE (β = −0.390, p < 0.001), while PE was negatively related to EB (β = −0.086, p < 0.05). PE was confirmed as a partial mediator in the NE-EB relationship (indirect effect = 0.034). Furthermore, LPA identified three distinct NE profiles: an “Emotionally Stable” group (16.86%), a “Transition Risk” group (51.33%), and an “Anxious-Distress” group (31.81%), with these profiles exhibiting significant differences in both EB (F = 65.088) and PE (F = 55.241).ConclusionFemale university students can be classified into three distinct emotional profiles (“Emotionally Stable,” “Transition Risk,” and “Anxious-Distress”), which are significantly associated with different levels of physical exercise and problematic eating behaviors. In addition, NE is not only directly associated with EB but also indirectly linked to it by reducing engagement in PE. This finding indicates that health interventions targeting female college students with high NE should, in addition to emotional management, actively promote the development of PE habits to effectively block the pathway from NE to unhealthy eating behaviors. The conclusions should be considered in light of the study’s cross-sectional design and its reliance on a single-item measure for PE.